Intelligent Self-Driving Car Architecture: Integrating AI and Machine Learning for Autonomous Mobility Systems - Manish Khute; Dr. Vijayalaxmi biradar (Revista Electronica de Veterinaria, 2025)
The evolution of autonomous vehicles (AVs) has been a transformative journey, marked by significant advancements in sensor technologies, computational power, and algorithmic complexity. Early developments in AVs were primarily focused on automating basic driving tasks, such as cruise control and lane-keeping assistance. However, the advent of more sophisticated sensors like LiDAR, radar, and high-resolution cameras, combined with powerful onboard computing systems, has paved the way for vehicles capable of full autonomy. In recent years, companies like Waymo and Tesla have made notable strides in deploying AVs in real-world environments.